The Dreams of Interpretation : A Century down the Royal Road - Liu, Catherine (Book collections on Project MUSE., 2007)
Rethinking the importance of Sigmund Freuds landmark book The Interpretation of Dreams a century after its publication in 1900, this work brings together psychoanalysts, philosophers, cultural theorists, film and visual theorists, and literary critics in a compilation of the best clinical and theoretical work being done in psychoanalysis today.